Numerical Analysis of The Effects of Propeller High Thrust Distribution on Propulsion System Performance - Sandjaja, Irfan Eko; Ariana, I Made; Erwandi, Erwandi; Indiaryanto, Mahendra; Muryadin, Muryadin; Adietya, Berlian Arswendo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
High ship propulsion performance is the main goal of designers, propeller is one component of the propulsion system that also affects the performance of the propulsion. In propeller planning, it is necessary to pay attention to the efficiency of the propeller, in addition to reducing ship operating costs and reducing CO2 gas emissions which is one of the requirements for ships built above 2013, the rules have been made into the Energy Efficiency Design Index (EEDI) standard. At this time the propeller that is widely used is the B Series propeller including the propeller design used on mini LNG ships, namely the B6.40 propeller, the B Series propeller has a pitch character from the Wageningen Propeller Series study. Innovations are made to get better propeller efficiency by varying the pitch distribution. The B6.40 propeller of the standard constant pitch type was modified to B6.40 variable pitch (high thrust). Propellers with high thrust have better efficiency especially for non-fast boats. This study was conducted to obtain the best propeller efficiency of a constant pitch propeller and three high thrust propeller units using Numeca's Computational Fluid Dynamics (CFD) numerical self-propulsion test. For validation of the simulation program by comparing the results of the open water test B6.40 Wageningen while resistance validation by comparing the ship resistance model test. The results of the self-propulsion test using Disc Actuator show that the propulsion coefficient (PC) of Modified-2 and Modified-3 high thrust propellers is better when compared to constant pitch. The magnitude of the increase in PC value reaches ± 4% higher than the constant pitch type on the Modified-3 propeller.